2018
DOI: 10.1194/jlr.d083261
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structural multiclass lipidomics using differential mobility: electron impact excitation of ions from organics (EIEIO) mass spectrometry

Abstract: We report a method for comprehensive structural characterization of lipids in animal tissues using a combination of differential Ion mobility spectrometry (DMS) with electron-impact excitation of ions from organics (EIEIO) mass spectrometry. Singly charged lipid ions in protonated or sodiated forms were dissociated by an electron beam having a kinetic energy of 10 eV in a branched radiofrequency ion trap. We established a comprehensive set of diagnostics to characterize structures of glycerophospholipids, sphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 31 publications
1
77
1
1
Order By: Relevance
“…It is evident that fatty acyls at the sn-1 position show lower diversity than those at the sn-2 position, with C16:0 and C18:0 as two high frequency groups. Although it has been suggested that the sn-2 position is preferred by polyunsaturated acyl chains, 29,44 our data quantitatively show that many of them still consist of minor sn-isomers, such as PC 20:4/ 16:0 (4%) and PC 22:4/18:0 (9%). For unsaturated PCs, about 60% were identied for C]C locations.…”
Section: An Lc-ms/ms Workow For the Analysis Of Pcs Down To Snand C]contrasting
confidence: 47%
See 1 more Smart Citation
“…It is evident that fatty acyls at the sn-1 position show lower diversity than those at the sn-2 position, with C16:0 and C18:0 as two high frequency groups. Although it has been suggested that the sn-2 position is preferred by polyunsaturated acyl chains, 29,44 our data quantitatively show that many of them still consist of minor sn-isomers, such as PC 20:4/ 16:0 (4%) and PC 22:4/18:0 (9%). For unsaturated PCs, about 60% were identied for C]C locations.…”
Section: An Lc-ms/ms Workow For the Analysis Of Pcs Down To Snand C]contrasting
confidence: 47%
“…These include electron impact excitation of ions from organics (EIEIO), 23 ozone-induced dissociation (OzID), [24][25][26] and ultraviolet photodissociation (UVPD). 27,28 All these developments greatly expand the toolbox for lipid analysis; more importantly, they not only provide rst-time analysis of lipidomes at the isomer level 11,19,[28][29][30] but also demonstrate the link between altered isomer compositions with disease quantitatively and spatially. [31][32][33][34] Radical-directed fragmentation has attracted increasing attention in MS/MS method development due to its unique capabilities in differentiating structural isomers of biomolecules, which otherwise cannot be obtained from chargedirected fragmentations typically seen from CID.…”
Section: Introductionmentioning
confidence: 99%
“…However, an ozone source may create unwanted hazards, the ionisation efficiency of ozonolysis is reportedly reduced in positive ion mode, and the high capillary voltage reduces sensitivity (43). Comprehensive structural characterization of lipids can also be performed using electron induced dissociation (EID) in combination with differential ion mobility spectrometry [also referred to as electron-impact excitation of ions from organics (EIEIO)] (44,45). Our assignment of the second double bond in murine brain sphingadiene to the C14-C15 position is in agreement with three publications from the late 1960s in which chemical derivatisation techniques coupled to thin-layer or gas chromatography were used to determine double bond positions in d18:2 SM species of human plasma and aorta samples (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…spectra from EID can identify lipid class, number of double bonds, and regio-isomers, although the precise position(s) of double bonds can be difficult to isolate using EID, since single bond fragments interfere with double bond diagnostic peaks(44). An important caveat regarding the general applicability of UVPD-MS/MS and other complex dissociation techniques described above is the complexity of data analysis.…”
mentioning
confidence: 99%
“…While this is an elegant method of determining double-bond regioisomers, it requires an adaptation of the instrument (the introduction of ozone into the collision cell) that is not yet commercially available. The use of electronimpact excitation of organic ions (EIEIO) at a kinetic energy of 10 eV has shown promise for the determination of fatty acyl sn positions, fatty acyl double-bond positons, and even double-bond conformations in glycerophospholipids (including plasmalogens), glycerolipids, and sphingolipids [81]. This is achieved using a branched radiofrequency (RF) ion trap EIEIO device that delivers selective fragments for separating the aforementioned types of isomers.…”
Section: Structure Elucidationmentioning
confidence: 99%